2019
DOI: 10.2478/mjhr-2019-0012
|View full text |Cite
|
Sign up to set email alerts
|

Significance Of Nutritional Value Of Fish For Human Health

Abstract: Nutrients are the substances which give nourishment to the body and promote growth. These nutrients are present in varieties of foods in various amounts. Fish is a source of aquatic food which can both be farmed and wild caught. Fish is rich in macronutrients: proteins, lipids and ash and micronutrients: vitamins and minerals. Proteins in the fish have immunoglobins that acts as defense mechanism against viral and bacterial infections and prevent protein calorie malnutrition. Lipids mainly LC n-3 PUFAs like EP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
78
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 16 publications
(15 reference statements)
0
78
0
11
Order By: Relevance
“…Regular consumption of fish, especially those high in n-3 poly unsaturated fatty acids (PUFA), also reduce incidences of, for example, diabetes mellitus, systemic arterial hypertension, central obesity and hyper-lipidemia [ 9 , 10 ], and seem to positively influence intestinal microbiota [ 11 ]. Furthermore, the macro nutrient content of fish with regard to protein is 15–20% and fish contains all the essential amino acids [ 12 ], which is beneficial for the diet as the sulphur-containing amino acids, cysteine and methionine, are absent in plant protein. Furthermore, proteins from fish have a high degree of digestibility i.e., 85–95% [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regular consumption of fish, especially those high in n-3 poly unsaturated fatty acids (PUFA), also reduce incidences of, for example, diabetes mellitus, systemic arterial hypertension, central obesity and hyper-lipidemia [ 9 , 10 ], and seem to positively influence intestinal microbiota [ 11 ]. Furthermore, the macro nutrient content of fish with regard to protein is 15–20% and fish contains all the essential amino acids [ 12 ], which is beneficial for the diet as the sulphur-containing amino acids, cysteine and methionine, are absent in plant protein. Furthermore, proteins from fish have a high degree of digestibility i.e., 85–95% [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the macro nutrient content of fish with regard to protein is 15–20% and fish contains all the essential amino acids [ 12 ], which is beneficial for the diet as the sulphur-containing amino acids, cysteine and methionine, are absent in plant protein. Furthermore, proteins from fish have a high degree of digestibility i.e., 85–95% [ 12 , 13 ]. Studies have shown positive health effects as a result of fish protein intake e.g., by decreasing the risk of metabolic syndromes and increasing insulin sensitivity [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…DHA is important for optimal brain and neurodevelopment in children, while on the other hand, EPA helps in improving cardiovascular health overall. Fatty acids also play an important role in membrane mediated processes such as osmoregulation, nutrient assimilation, and transport [95]. Fish are the most important sources of these fatty acids; fatty fish, such as sardines, mackerel, anchovies, and some salmon species, are rich in EPA and DHA.…”
Section: Global Fish Consumption and Its Nutraceutical Market: Currenmentioning
confidence: 99%
“…It has been reported that fish protein has a greater satiety effect than other sources of animal proteins like beef and chicken. Around 60% of people from developing countries depend upon fish for over 30% of their animal protein supplies [95,101]. Moreover, fish proteins are highly digestible as well as a rich source of peptides and essential amino acids that are limited in terrestrial meat proteins.…”
Section: Proteins and Amino Acidsmentioning
confidence: 99%
See 1 more Smart Citation